Kinematical analysis of the V2 ski skating technique: A longitudinal study - Losnegard, T.; Myklebust, H.; Ehrhardt, A.; Hallén, J. (Journal of Sports Sciences, 2017)
To characterise timing of movements and evaluate performance effects of technique alterations in V2 ski skating, 13 elite male cross-country skiers (age, 23 ± 2 years; stature, 182 ± 6 cm; body mass, 76 ± 8 kg; V2 V?O2max, 79.3 ± 4.4 mL/kgmin) were tested four times during the preparation and competition phase on a roller ski treadmill. Each test consisted of submaximal intensities of exercise for determination of oxygen cost followed by one 1000-m performance test. Hip movement (from accelerometer data) and joint angles (2D video) were determined for high-intensity exercise (6° and 3.5 m/s; ~ 97-100% of V?O2peak). Each ski thrust consisted of three phases: gliding phase (18-50% of cycle time), poling phase (50-70% of cycle time), and kick phase (70-78% of cycle time). Flexion/extension of the hip initiated all phases, followed by the respective joints in legs and arms. Mixed-model analysis, adjusting for systematic time-point effects, identified that both reduced vertical hip acceleration and increased cycle time gave a small likely reduction in oxygen cost and 1000-m time. In conclusion, well-developed hip movement is a key characteristic of the V2 technique for elite-standard skiers` long-term performance development.